Design & Implement a Dynamic & Adaptive Grammar Learning Tools - Nur Amila Aina, Abdul Manap; Nadia, Refat; Hafizoah, Kassim; Rahman, Md. Arafatur (Penerbit Universiti Malaysia Pahang, 2016)
Design and Implement a Dynamic & Adaptive Grammar Learning Tool is aimed to identify the level of students learning in grammar precisely in tense. The learning process is well adapted into the mobile smartphones and tablets application especially for android users as an attractive and dynamic tool. This project is exposed to the adaptability of students based on their level of understanding in Grammar, thus can help and improves their grammar effectively.